LINGUOCULTURAL STUDY OF PHRASEOLOGICAL UNITS WITH SEVERAL SOMATIC COMPONENTS IN ENGLISH AND UZBEK LANGUAGES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article discusses linguocultural studies of phraseological units with several somatic components in Uzbek and English languages. A phraseological unit or phrase, although the phrase is very ancient in origin, the history of the science of phraseology goes back several hundred years. Phraseologisms are the wealth of a nation, and their sources are closely related to nature, economic structure, history, culture, way of life, oral literature, fiction, art, science, and customs of the place where a particular people lives.